Conferencia de filosofía y derecho en homenaje Carlos Cossio Werner Goldschmidt - Raffo, Julio César (2008)
In this lecture, César Raffo talks about the works and the life of Carlos Cossio. He divides his presentation into three parts: how he discovered and met this philosopher, some key concepts in the thought of Cossio, and lastly he finishes by considering some aspects of the academic life of Cossio in the Law School. Then, Miguel Ángel Ciuro Caldani presents the biography of Werner Goldschmidt and analyzes his contribution to the modern times